The relevance, importance and applicability of corporate social and environmental responsibility: South African case studies - Louw, Marie-Louise (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.